Using Computer Programs for Language Sample Analysis. - Pezold, Mollee J.; Imgrund, Caitlin M.; Storkel, Holly L. (Language, Speech & Hearing Services in Schools, 2020)
Purpose: Although language sample analysis is widely recommended for assessing children's expressive language, few school-based speech-language pathologists routinely use it, citing a lack of time, resources, and training (Pavelko, Owens, Ireland, & Hahs-Vaughn, 2016). The purpose of this clinical tutorial is (a) to describe options for language sample analysis using computer programs and (b) to demonstrate a process of using language sample analysis focused on the assessment of 2 preschool children as case studies. Method: We provide an overview of collecting and analyzing child language samples and describe 3 programs for language sample analysis: 2 dedicated software programs (Computerized Language Analysis [MacWhinney, 2000] and Systematic Analysis of Language Transcripts [Miller & Iglesias, 2015]) and 1 protocol for using word processing software to analyze language samples (Sampling Utterances and Grammatical Analysis Revised; Pavelko & Owens, 2017). We also present analysis results from each program for play-based language samples from 2 preschool children and detailed analysis of the samples with potential treatment goals. Results: Each program offers different analyses, comparison databases, and sampling contexts. We present options for additional analysis, clinical interpretations, and potential treatment goals based on the 2 preschool cases. Conclusion: Clinicians can use computer programs for language sample analysis as part of a process to make naturalistic language assessment more feasible.